(untitled) (Physical Education, Health and Social Sciences, 2025)
The purpose of this study is to examine how role ambiguity affects academic disengagement as a result of role ambiguity. Moreover, this study examines the impact of social support in relation to role ambiguity as well as burnout in relation to role ambiguity as well. Two hundred and thirty-one academicians were asked to complete a self-assessment questionnaire.Role ambiguity is linked to disengagement, showing that unclear job roles decrease engagement. There is also evidence to suggest that social support plays an important role in influencing this relationship, potentially leading to a reduction in disengagement when roles are unclear. It also makes recommendations for future research for higher education leaders and scholars.